A new species of Pseudopaludicola Miranda-Ribeiro (Leiuperinae: Leptodactylidae: Anura) from the Cerrado of southeastern Brazil with a distinctive advertisement call pattern - de Carvalho, Thiago Ribeiro (Zootaxa, 2012)
A new species of Pseudopaludicola is described from the Cerrado of southeastern Brazil. The new taxon is diagnosedfrom the P. pusilla species group by the absence of either T-shaped terminal phalanges or toe tips expanded, and promptlydistinguished from all (13) recognized taxa currently assigned to Pseudopaludicola by possessing isolated (instead of regular call series), long (117–187 ms) and non-pulsed advertisement calls.